On effectiveness of «soft» law the case of un treaty bodies instruments (International relations and international law Journal, 2018)
The article discusses the capacities of international law to provide for «rule of law» internationally given the lack of comprehensive enforcement mechanisms and critically assess the concept and practices of «soft» law in this context.The author starts by surveying the probable explanations why states observe international legal norm even without a proper enforcement that would include the interest of the powerful, convenience, desire for better international socialization. The article then proceeds to discuss whether these arguments apply to «soft» law«.Further, the author deals with the question of how international human rights law is similar to and/or different from other International law and examines the case of the «Views» and «General Comments» of the UN human rights treaty bodies to find out whether it is an effective mechanism to protect human rights and whether they make (if at all) states to adhere to their human rights commitments both domestically and internationally.Key words: international law, soft law, obedience without enforcement, human rights law, UN treaty bodies, legal scholarship, «Views» and «Comments» of UN treaty bodies, non-binding international norms, non-binding instruments.